Frailty Predicts Decreased Survival, More Complications, and Higher Hunt & Hess and Fisher Scores Following an Aneurysmal Subarachnoid Hemorrhage. (1st September 2019) - McIntyre, Matthew; Patel, Vikas; Long, Andrew; Vonhoof, Alex; Li, Boyi; Afridi, Adil; Halabi, Mohamed; Al-Mufti, Fawaz; Gandhi, Chirag D; Santarelli, Justin G; Schmidt, Meic H; Cole, Chad D; et al.
Abstract: INTRODUCTION: Aneurysmal SAH (aSAH) is associated with high rates of morbidity and mortality, yet frailty's effect on aSAH outcomes has not been explored. The most common method of measuring frailty is via the modified frailty index (mFI). We hypothesized that increasing frailty is associated with poorer outcomes following an aSAH. METHODS: Patients with aSAH were retrospectively identified from angiogram records. The cohort was divided into nonfrail (mFI = 0-1) and frail (mFI = 2) groups based on prehemorrhage characteristics. Primary outcomes were mortality, discharge location, complications (without vasospasm), and vasospasm. Groups were compared using Fishers exact or Mann-Whitney tests, and Kaplan-Meier survival curves were generated for Log-Rank analysis. RESULTS: A total of 217 patients with aSAH were identified, 57 of whom were classified as frail (mean mFI = 1.0 ± 0.08). The average Hunt & Hess (HH) and Fisher scores were 2.9 ± 0.09 and 3.7 ± 0.04, respectively. 167 (77%) of patients had = 1 complication, 124 (57.1%) developed vasospasm, but only 41 (18.9%) died, and 74 (34%) were discharged home. Frail patients were significantly older (66 vs 55 yr; P  < .0001), had higher rates of hyperlipidemia (OR = 2.2; 95% CI: 1.2-4.3; P  = .0219), and had higher HH ( P  = .005) and Fisher ( P  = .0255) scores. Frail patients were less likely to receive an intervention (OR = 0.3; 95% CI: 0.1-0.6; P  = .0056), less likely to be discharged home (OR = 0.32; 95% CI: 0.16-0.68; P  = .0020), had a higher mortality rate (OR = 2.4; 95% CI: 1.2-5; P  = .0183), and were more likely develop a complication (OR = 2.6; 95% CI: 1.1-6.6; P  = .0277). Log-Rank testing of Kaplan-Meier curves found that frail individuals have a significantly decreased survival compared to non-frail individuals (X2 (1) = 6.939; P  = .0084). There were no differences in vasospasm rates between groups. CONCLUSION: Frailty is an independent predictor of higher HH and Fisher scores following aSAH, along with lower rates of aneurysm intervention, discharge home, and survival. This relationship has never been demonstrated for aSAH and is valuable for risk stratification and prognostication in aSAH patients.